The Enhancing Nurses’ and Midwives’ Competence in Providing Spiritual Care through Innovative Education and Compassionate Care (EPICC) Network - (:unkn) unknown (My University, 2026)
The Enhancing Nurses’ and Midwives’ Competence in Providing Spiritual Care through Innovative Education and Compassionate Care (EPICC) Network exists to sustain, develop and advance the Erasmus+ KA2 Grant Agreement Number: 2016-1-UK01-KA203-024467 project and all its deliverbales which were submitted by the end of 2019.